2020
DOI: 10.1097/md.0000000000019374
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of ankle-brachial index, vibration perception threshold, and current perception threshold to glycemic variability in type 2 diabetes

Abstract: To explore the relationship of glycemic variability with lower extremity arterial disease (LEAD) and diabetic peripheral neuropathy (DPN). Seventy-eight patients with type 2 diabetes were enrolled. All patients underwent 72-hour dynamic blood glucose monitoring and obtained mean amplitude of glycemic excursions (MAGE), mean of daily differences (MODD), standard deviation of blood glucose (SD), largest amplitude of glycemic excursion (LAGE), mean blood glucose (MBG), T≥10.0 (percentage of time for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Generally, our findings are in line with the few studies on the associations of CGMbased daily GV with arterial stiffness 105 , cIMT 106 , and ABI 107 . Since we observed a moderately strong correlation between CGM-assessed GV and the 1-hour OGTT value (Chapter 2), the studies that link the latter metric to arterial stiffness 108,109 and CVD 110 could be considered further support for daily GV as a determinant of CVD.…”
Section: Daily Glucose Variability As Determinant Of Cardiovascular Diseasesupporting
confidence: 92%
“…Generally, our findings are in line with the few studies on the associations of CGMbased daily GV with arterial stiffness 105 , cIMT 106 , and ABI 107 . Since we observed a moderately strong correlation between CGM-assessed GV and the 1-hour OGTT value (Chapter 2), the studies that link the latter metric to arterial stiffness 108,109 and CVD 110 could be considered further support for daily GV as a determinant of CVD.…”
Section: Daily Glucose Variability As Determinant Of Cardiovascular Diseasesupporting
confidence: 92%
“…One study found that increasing MAGE was a significant independent contributor to DPN in type 2 diabetes mellitus patients 27 . In contrast, another study showed that MAGE and SD were not associated with DPN 29 . The conflicting results might be attributable to the different diagnostic criteria of DPN and different types of diabetes assessed.…”
Section: Discussionmentioning
confidence: 85%
“…ABI is the ratio of the systolic blood pressure of the ankle artery (posterior-tibial or dorsal-foot artery) to the ipsilateral brachial artery [20]. All patients in this study had ABI tested by professionally trained medical staff, and the pressures in the bilateral upper limb brachial artery, lower limb dorsalis pedis artery, and posterior tibial artery were measured using an ultrasonic Doppler blood flow detector (VistaAVS, Summit Doppler Systems, USA).…”
Section: Abi Determinationmentioning
confidence: 99%